An altered composition of the microbiome in microscopic colitis is driven towards the composition in healthy controls by treatment with budesonide. (3rd April 2019) - Rindom Krogsgaard, Laura; Kristian Munck, Lars; Bytzer, Peter; Wildt, Signe
Abstract: Background and aim: Microscopic colitis (MC) is an inflammatory disease of the bowel, hypothetically induced by an immunologic response to a luminal microbial agent. We aimed to characterize the microbiome composition in MC and subtypes collagenous colitis (CC) and lymphocytic colitis (LC) and to identify a possible microbial effect of treatment. Method: Stool samples were collected from MC patients prior to treatment, at 8 weeks (during treatment) and at 16 weeks (after treatment), and from healthy controls, not receiving treatment, at matched time-points. Microbiome composition was analyzed by sequencing of the 16S and 18S genes. Differences between patients and controls were analyzed by Shannon's diversity index (mean, standard deviation (SD)) and principal coordinate analysis (PCoA) complemented with a permanova test of UniFrac distances. Results: Ten LC patients, 10 CC patients and 10 controls were included. By PCoA, the bacterial composition in MC patients differed from controls at baseline ( p = .02), but not during and after treatment ( p = .09 and p = .33, respectively). At baseline, bacterial diversity was lower in MC patients compared to controls (2.5, SD: 0.5 vs 3.5, SD: 0.3, p < .05). Diversity in MC patients increased during (3.0, SD: 0.6) and after treatment and (2.9, SD: 0.5) compared with baseline ( p < .01). Eukaryotes were detected in fewer samples from MC patients compared with controls (11/20 (55%) vs. 9/10 (90%), p = .06) with no effect of treatment. Conclusion: Microbiome composition is altered in MC patients. During and after treatment with budesonide the microbiome composition in MC patients was driven towards the composition in healthy controls.